Carboxymethyl chitosan/gelatin/hyaluronic acid blended-membranes as epithelia transplanting scaffold for corneal wound healing. (15th July 2018) - Xu, Wenhua; Wang, Zheying; Liu, Ying; Wang, Liping; Jiang, Zhiwen; Li, Tong; Zhang, Wenhua; Liang, Ye
Highlights: Preparation of carboxymethyl chitosan (CMCTS)-blended membranes as corneal epithelial cell (CEpC) carriers. Evaluation of characteristics, biodegradability and cytocompatibility of CMCTS-blended membranes. A combination treatment effect of CEpCs/CMCTS membranes could clearly promote corneal alkali burn wound healing. Abstract: There is an unmet need for an optimal scaffold as cell transplantation carrier to induce corneal reconstruction. In this study, a blend membrane was prepared with carboxymethyl chitosan (CMCTS), gelatin, and hyaluronic acid. To investigate its cytocompatibility, primary rabbit corneal epithelial cells (CEpCs) were seeded on it and growth and proliferation were evaluated. The blend membrane was found to be transparent, biodegradable, and suitable for CEpCs attachment and proliferation, which could maintain the epithelial cell-like protein expression of CEpCs. The combination of CEpCs and CMCTS-blended membrane (CEpCs/CMCTS membrane) was used to treat alkali-induced corneal damage in rabbits and healing effects were evaluated by visual observation, slit lamp, hematoxylin-eosin and immunofluorescence staining. CEpCs/CMCTS membrane could improve corneal epithelial reconstruction significantly and restore cornea transparency and thickness. Hence, this combination treatment may serve as a rapid and effective way for corneal wound healing.